2009
DOI: 10.1016/j.neuroscience.2009.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal spine-associated Rap-specific GTPase-activating protein induces enhancement of learning and memory in postnatally hypoxia-exposed mice

Abstract: Spine-associated Rap-specific GTPase-activating protein (SPAR) is a postsynaptic protein that forms a complex with postsynaptic density (PSD)-95 and N-methyl-D-aspartate receptors (NMDARs), and morphologically regulates dendritic spines. Mild intermittent hypoxia (IH, 16.0% O2, 4 h/day for 4 weeks) is known to markedly enhance spatial learning and memory in postnatal developing mice. Here, we report that this effect is correlated with persistent increases in SPAR expression as well as long-term potentiation (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
(56 reference statements)
3
21
0
Order By: Relevance
“…These studies are in agreement with previous studies, which showed that both proteins are involved in morphological rearrangements in neurons (Murai et al, 2003;Pak et al, 2001). Recent research has implicated SPAR1 also in NMDA-induced excitotoxicity and neurodegeneration (Wu et al, 2007), as well as in synaptic plasticity following hypoxia (Lu et al, 2009). The pathophysiological relevance of synaptic SPAR expression, however, is just beginning to emerge.…”
Section: ;supporting
confidence: 91%
See 1 more Smart Citation
“…These studies are in agreement with previous studies, which showed that both proteins are involved in morphological rearrangements in neurons (Murai et al, 2003;Pak et al, 2001). Recent research has implicated SPAR1 also in NMDA-induced excitotoxicity and neurodegeneration (Wu et al, 2007), as well as in synaptic plasticity following hypoxia (Lu et al, 2009). The pathophysiological relevance of synaptic SPAR expression, however, is just beginning to emerge.…”
Section: ;supporting
confidence: 91%
“…Recent research has implicated SPAR1 also in NMDA‐induced excitotoxicity and neurodegeneration (Wu et al. , 2007), as well as in synaptic plasticity following hypoxia (Lu et al. , 2009).…”
Section: Structural Plasticity At Dendritic Spines Of Pyramidal Neuromentioning
confidence: 99%
“…In recent studies, we showed that a short (5 min) neonatal hypoxia in rats can activate endogenous brain neurogenesis that secondarily gives rise to a significant functional gain [9], [12]. In good agreement, Lu et al [33] reported that postnatal exposure to mild intermittent hypoxia (16% O2, 4 h/day for 4 weeks) enhances spatial learning and memory in developing mice. However, whereas cell mechanisms involved remain poorly understood, no information was available on the long-term consequences on the aging brain of the surnumerary neurons produced in early life.…”
Section: Discussionsupporting
confidence: 72%
“…The signaling pathways that link glutamate receptor and PSD‐95 to the postsynaptic actin cytoskeleton is the Spine‐associated Rap GTPase activating protein (SPAR). SPAR promotes actin polymerization by inhibiting Rap, a small GTPase protein, resulting in spine enlargement and enhanced stability of the spine (Hall, 1992; Jeon et al, 2007; Lu et al, 2009; Matus, 2000; Tada and Sheng, 2006). The increase in the amount of PSD‐95 and SPAR has been reported to be associated with the increase of NR2A‐containing NMDA receptor and the maturity of dendritic spine (Petralia et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reduction in the amount of NR2B‐containing NMDA receptors, by disrupting the NR2B/PSD‐95 complex, is accompanied by a dramatic reduction in the induction of long‐term potentiation (LTP) (Gardoni et al, 2009). While SPAR antisense‐treated mice exhibit impaired acquisition of the Morris water maze navigating task, as well as impairment in memory retention of probe trails following training, there is a reduction in the hippocampal LTP without any alterations of the basal synaptic transmission (Lu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%